Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar Tentang Siklus Air Siswa SD - Muslimin Muslimin; Nurul Mukhlisa; A. Irma Amalia Mihrab (STKIP Andi Matappa Pangkep, 2023)
This study aims to determine the process and results of the application of the Problem Based Learning learning model can improve the learning process about the water cycle of class V UPT SD Negeri 228 Pinrang students. This research uses a qualitative approach and the type of research used is Classroom Action Research (PTK). The subjects of the study were class teachers and students totalling 22. The analytical techniques used ate data condensation, data presentation, and verification. In cycle I, the results of research on the learning process from the teacher aspect were in good qualifications (B), from the student aspect were in sufficient qualifications (C) and learning outcomes were in sufficient qualifications (C). While in cycle II the results of research on the learning process from the teacher's aspect were in good qualifications (B), from the student's aspect were in good qualifications (B) and the learning outcomes test was in good qualifications (B). The conclusion of this research is that the application of Problem Based Learning learning model about water cycle can improve the learning process and learning outcomes of class V students of UPT SD Negeri 228 Pinrang.